A Case of Post-trauma Dysphagia: Peculiar Swallowing Dynamics Due to Associated Laryngeal Paralysis - Sugi, Takafumi (Prog Rehabil Med, 2020)
BACKGROUND: Associated laryngeal paralysis (ALP) is defined as vagus nerve impairment combined with other lower cranial nerve paralysis. Traumatic ALP is reported infrequently. CASE: A 72-year-old man was injured on the back of the head when a large tree fell on him; he was admitted to a general hospital, where he was diagnosed with brain concussion and Guillain-Barre syndrome (GBS). The patient developed aspiration pneumonia due to severe dysphagia. Although he underwent treatment and rehabilitation for 6 months, some disabilities persisted, and a percutaneous endoscopic gastrostomy tube was placed. Six months after the accident, the patient was transferred to our rehabilitation hospital. Videoendoscopic examination and videofluoroscopy revealed persistent upper esophageal sphincter (UES) opening, left dominant bilateral IX and X nerve paralysis, and left XII nerve paralysis; moreover, these examinations showed that the swallowing reflex was absent, although a bolus could pass through the UES. We suspected that the patient’s condition was not GBS and performed head computed tomography and magnetic resonance imaging; these revealed a bone fracture at the skull base. Consequently, the patient’s diagnosis was changed to bilateral ALP. He received swallowing rehabilitation for 2 months and could orally consume alternative nutrition. Finally, the patient was able to eat orally texture-modified foods (Food Intake LEVEL Scale level 8). DISCUSSION: While post-trauma dysphagia due to bilateral ALP might be severe, patients can regain the ability to eat orally if clinicians understand the etiology of dysphagia and provide appropriate swallowing rehabilitation techniques, including patient position adjustment while eating and selection of food textures.